Improvement of Mathematical Learning Activities And Results Through PBL and Congretting Media in Class 1st Students - Siti Aminah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The researchers made improvements by applying a scientific approach with the Problem Based Learning model and concrete media. This type of research is classroom action research. which consists of two cycles, each cycle carried out with one meeting. Each cycle consists of the planning, action, observation and reflection stages. The research subjects were grade I students of SDN Pende 02. The data collection techniques used test and non-test techniques obtained from observations and documentation. The results of this study are the use of concrete media and problem based learning can improve student learning outcomes on the subject of addition and subtraction of numbers in grade I SDN Pende 02, Kersana District, Brebes Regency. In the first cycle of students who completed there were 14 students, the percentage of classical student learning completeness was 63.63%. In cycle II students who completed an increase of 20 students, students' reading completeness was 90.90%. So it can be concluded that student learning outcomes have increased and are said to be complete.